2022
DOI: 10.1016/j.amjsurg.2021.10.026
|View full text |Cite
|
Sign up to set email alerts
|

A potential novel biomarker in predicting lymph node metastasis of gastric signet ring cell carcinoma: A derived monocyte to lymphocyte ratio

Abstract: Background: This study is designed to evaluate the predictive value of derived monocyte to lymphocyte ratio (dMLR), neutrophil to lymphocyte ratio (NLR) and eosinophil to lymphocyte ratio (ELR) for lymph node metastasis (LNM) in gastric signet ring cell carcinoma (SRCC) patients. Methods: We carried out a retrospective analysis for 203 eligible patients who underwent radical gastrectomy between January 2011 and September 2020. Results: The diagnostic sensitivity and specificity for dMLR were 60.3% and 72.2%, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…13 Tong et al used the derived monocyte-to-lymphocyte ratio for predicting LNM in patients with gastric signet ring cell carcinoma. 21 FLR, combined with hemagglutination and inflammation markers, have a potential prognostic value in different types of cancers, such as non-small cell lung cancer, esophageal cancer, liver cancer, and head and neck adenoid cystic carcinoma. [16][17][18][19] In addition, Huang et al found that a high FLR level was a risk factor for peritoneal metastasis in GC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Tong et al used the derived monocyte-to-lymphocyte ratio for predicting LNM in patients with gastric signet ring cell carcinoma. 21 FLR, combined with hemagglutination and inflammation markers, have a potential prognostic value in different types of cancers, such as non-small cell lung cancer, esophageal cancer, liver cancer, and head and neck adenoid cystic carcinoma. [16][17][18][19] In addition, Huang et al found that a high FLR level was a risk factor for peritoneal metastasis in GC.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters were measured within 1 week before surgery, and the results of the first blood test after admission were considered the main results. 21 was identified using a contrast-enhanced abdominal CT scan. Based on previous studies, cN+ was defined as lymph nodes with a short-axis diameter of ≥ 8 mm or a long-axis diameter of ≥ 10 mm 23,24 and cN0 as the absence of LNM.…”
Section: Data Collectionmentioning
confidence: 99%
“…In terms of sensitivity analysis, we incorporated the quartile of PALR in the multivariate analysis. We used AUC, decision curve analysis (DCA), and the calibration curves to evaluate the nomogram as previously described ( 23 25 ). The internal validation of the model was performed via a bootstrap resample approach (1000 samples), together with the calculation of a corrected concordance index (C-index) ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…All of the blood samples were collected before EVT. We documented neutrophil count (N),12 13 white blood cell count (W),13 eosinophil count (E),14 monocyte count (M),5 lymphocyte count (L),5 and platelet count (P/PLT),5 and calculated the following according to the above indicators: neutrophil to lymphocyte ratio (NLR),4 platelet to lymphocyte ratio (PLR),4 platelet to neutrophil ratio (PNR),5 6 platelet to white blood cell ratio (PWR)6, platelet to monocyte ratio (PMR),15 lymphocyte to monocyte ratio (LMR),16 monocyte to neutrophil ratio (MNR),5 eosinophil to lymphocyte ratio (ELR),17 and eosinophil to monocyte ratio (EMR) 18. NLR to platelet ratio (NLR/PLT) was calculated as the value of the ratio of NLR to platelets 19…”
Section: Methodsmentioning
confidence: 99%